2009
DOI: 10.1126/science.1171402
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency, Long-Range Coupling Between Prefrontal and Visual Cortex During Attention

Abstract: Electrical recordings in humans and monkeys show attentional enhancement of evoked responses and gamma synchrony in ventral stream cortical areas. Does this synchrony result from intrinsic activity in visual cortex or from inputs from other structures? Using paired-recordings in the frontal eye field (FEF) and area V4, we found that attention to a stimulus in their joint receptive field leads to enhanced oscillatory coupling between the two areas, particularly at gamma frequencies. This coupling appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

105
1,051
8
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,126 publications
(1,207 citation statements)
references
References 27 publications
105
1,051
8
10
Order By: Relevance
“…As a consequence, postsynaptic neuronal groups would receive spatially and temporally dense excitation, triggering a new chain of taskselective spiking output and potentially allowing to synchronize distant nodes of larger cognitive control network to a common underlying theta-rhythm. Although this scenario awaits to be tested directly, previous studies suggest that selective synchronization at theta-and/or higher γ-band frequencies among neuronal groups is indeed used by the brain to integrate and rapidly distribute task-relevant information (59,60). One interesting speculation relates the observed LFP thetaactivity in the ACC to theta-activity recorded from the frontal midline in human EEG/MEG studies.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, postsynaptic neuronal groups would receive spatially and temporally dense excitation, triggering a new chain of taskselective spiking output and potentially allowing to synchronize distant nodes of larger cognitive control network to a common underlying theta-rhythm. Although this scenario awaits to be tested directly, previous studies suggest that selective synchronization at theta-and/or higher γ-band frequencies among neuronal groups is indeed used by the brain to integrate and rapidly distribute task-relevant information (59,60). One interesting speculation relates the observed LFP thetaactivity in the ACC to theta-activity recorded from the frontal midline in human EEG/MEG studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some forms of dynamic grouping require attention, and it has been shown that attention strongly enhances gamma-band synchronization both within (Fries et al, 2001b) and between cortical regions (Gregoriou et al, 2009). Furthermore, in addition to any role that it has in grouping, attention may also affect amplification and suppression via its effect on the synchrony of inhibitory interneuron activities.…”
Section: Modulation That Synchronizes Responses To Rf Inputmentioning
confidence: 99%
“…Simultaneous recording from multiple intracortical areas in monkeys showed that the coherent higher frequency (beta and gamma bands) oscillations are linked to a broad variety of cognitive functions (12)(13)(14)(15)(16)(17)(18). Cortical oscillations at lower frequencies (theta and alpha bands) have also been discussed in terms of long-range integrative processes (19,20).…”
mentioning
confidence: 99%